O efeito estético espaço-temporal na obra de Paes Loureiro: uma confluência entre Água da fonte e Café Central – o tempo submerso nos espelhos - Araujo, Jorge Paulino Duarte de (2023)
This thesis deals with the analytical application of Wolfgang Iser's theory of aesthetic effect in two books by the poet and novelist Paes Loureiro: Água da fonte (2008) and Café Central - O tempo submerso nos espelhos (2011). Throughout this research, we aim to correlate space and time in the construction of poetry and romance. Our theoretical foundation is the thought of the German literary critic Wolfgang Iser, who, through his theory of aesthetic effect, presents reading as a changing process that seeks the synthesis of texts. In this sense, the text emerges as a possibility for the reader, when interacting with it, to formalize a suspensive perception, through an interactivity, generating another text. A communication with the text is established from the voids identified by the implicit reader, coming from the clues that the author left strategically placed in the texts, which makes the reader take the text out of an immobility. The characterization of space-time towards the aesthetic effect is fostered through the identification of the voids. The empty spaces produce ambiguities that stimulate the reader to seek interpretative solutions within his repertoire, and these spaces are detected by the imposition of the literary structure itself, guided by the sequence built in a plurissignificant way by the author. Regarding methodology, the aforementioned research understands that the theory of aesthetic effect is a practice that can account for an investigation on space and time, both in poetry and in the novel. To conclude this thesis, we understand that both the book of poetry and the novel can be concretized under the suspension of an "as if", two realities that carry literary potencies and do not contain a crystallized meaning